Species diversity, size and component arrangement in homegardens of North Bengal, India - Subba, Mohit; Sarkar, Biplov C.; Pala, Nazir A.; Shukla, Gopal; ., Vineeta; Chakravarty, Sumit (Indian Journal of Agroforestry, 2020)
The present study was carried out in the homegardens of northern part of West Bengal. The study reported species diversity, size and component arrangement in randomly selected 100 homegardens from north Bengal. The maximum species richness was 42 and minimum 12. The average size of the homegarden was 0.51 ha with maximum area of 2.66 ha and minimum 0.06 ha. Out of total surveyed 100 homegardens, 45 had 8-18 species, 47 had 18-28 species and 8 had 28-38 species. Betel nut (Areca catechu) was found most common in 84 homegardens and tomato (Lycopersicon esculentum) was least dominant in one homegarden. Animal component existed in 60% of the sampled households that included cattle (cows and goats), pigs, poultry and birds (hens and ducks). Ponds as a component of homegardens were observed in 11% of the homesteads whereas only animals in pond ecosystem of the homegarden were observed in only 2% of the household. The homegardens of north Bengal have good diversity and vital reservoir of unique genetic diversity, and can be handful in-situ-conservation units for local plant diversity conservation.